Membrane technologies for heavy metals removal from water and wastewater: A mini review - Abdullahi Haruna Birniwa; Shehu Habibu; Shehu Sa'ad Abdullahi; Rania Edrees Adam Mohammad; Abdulmalik Hussaini; Hamza Magaji; Baker Nasser Saleh Al-dhawi; Azmatullah Noor; Ahmad Hussaini Jagaba (Case Studies in Chemical and Environmental Engineering, 2024)
Clean water scarcity is an escalating global concern, necessitating the development of innovative membrane technologies. This mini review explores the multifaceted realm of membrane technology, a field increasingly engaging researchers and academics. Polymeric membranes find application in diverse domains, spanning gas separation, packaging films, protective coatings, and crucially, water purification techniques like reverse osmosis and various filtration methods. This review predominantly focuses on pressure-driven membrane processes, a classification evolving in selectivity from nanofiltration to microfiltration. It further dissects these processes based on natural and synthetic polymeric membranes. Notably, this work delves into the pivotal role of polymeric membranes in heavy metal water purification, emphasizing the evolving landscape of membrane technologies. Three notable membrane types under scrutiny are Mixed Matrix Membranes, Thin Film Layer Membranes, and membranes incorporating polymer inclusions. Their versatility and applications in diverse sectors showcase the burgeoning potential of polymeric membranes. Furthermore, this review outlines the future applications of polymeric membranes, delineating their indispensable role in nanofiltration, microfiltration, ultrafiltration, and complexation-enhanced ultrafiltration. The compelling attributes of reverse osmosis, forward osmosis, and pervaporation in advancing water purification are also expounded upon. The review culminates by providing an insight into the structural intricacies of polymeric membranes, shedding light on their diverse applications and their pivotal role in addressing the global water crisis. The dynamic and evolving landscape of membrane technology underscores the crucial need for continued research and innovation in this domain to tackle water pollution and scarcity effectively. As we venture further into the 21st century, the multifaceted applications of polymeric membranes are set to play an instrumental role in safeguarding our most precious resource—clean and sustainable water.